2015
DOI: 10.1371/journal.pone.0129967
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Runs of Homozygosity and Inbreeding in Jersey Cattle under Selection

Abstract: Inbreeding is often an inevitable outcome of strong directional artificial selection but on average it reduces population fitness with increased frequency of recessive deleterious alleles. Runs of homozygosity (ROH) representing genomic autozygosity that occur from mating between selected and genomically related individuals may be able to reveal the regions affecting fitness. To examine the influence of genomic autozygosity on fitness, we used a genome-wide association test to evaluate potential negative corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 50 publications
6
69
1
2
Order By: Relevance
“…In contrast, Maximini et al (2011) Although F ROH has already been used to confirm inbreeding depression of reproductive traits in cows (Bjelland et al, 2013;Kim et al, 2013Kim et al, , 2015Pryce et al, 2014) and pigs (Saura et al, 2015), the present report is the first to our knowledge that applies the same tool to sperm quality in any species. Numerous studies have documented that inbreeding depression (measured using F PED ) causes sperm quality defects in various species, including wild mammals (Shivaji et al, 1998;Asa et al, 2007;Ruiz-Lopez et al, 2010), domestic cats (Pukazhenthi et al, 2006), and horses (van Eldik et al, 2006).…”
Section: Estimation Of Genome-wide Inbreeding Depressionmentioning
confidence: 77%
“…In contrast, Maximini et al (2011) Although F ROH has already been used to confirm inbreeding depression of reproductive traits in cows (Bjelland et al, 2013;Kim et al, 2013Kim et al, , 2015Pryce et al, 2014) and pigs (Saura et al, 2015), the present report is the first to our knowledge that applies the same tool to sperm quality in any species. Numerous studies have documented that inbreeding depression (measured using F PED ) causes sperm quality defects in various species, including wild mammals (Shivaji et al, 1998;Asa et al, 2007;Ruiz-Lopez et al, 2010), domestic cats (Pukazhenthi et al, 2006), and horses (van Eldik et al, 2006).…”
Section: Estimation Of Genome-wide Inbreeding Depressionmentioning
confidence: 77%
“…Previous research in dairy cattle showed that the additive effects of regions of high frequency of ROH for yield traits and/or calving interval have positive covariances, such that it is beneficial for the region to be in a long homozygous stretch [62]. Kim et al [63] reported a similar result based on the regression of the most frequent haplotype on phenotype for multiple yield and fertility traits. Accumulation of inbreeding in parental lines is expected to result in an increase in the frequency of both favorable and deleterious haplotypes.…”
Section: Discussionmentioning
confidence: 95%
“…Genome-wide inbreeding metrics are not able to account for the fact that homozygosity or loss of genetic diversity may have very different effects. The presence of ROH at certain locations has been found to have detrimental effects in dairy cattle, while some may be inconsequential (Pryce et al, 2014;Kim et al, 2015). The frequency of ROH in dairy cattle is not uniform across the genome and may correlate with regions putatively under selection (Purfield et al, 2012;Zhang et al, 2015).…”
Section: Genetic Diversitymentioning
confidence: 99%